Variations of English Pronunciation and Errors Made by the English Department Students Year 2012 Faculty of Cultural Sciences Universitas Gadjah Mada - , SULISTYANINGRUM; , Dra. Sharifah Hanidar, M.Ed. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research focuses on English pronunciation made by English Department Students year 2012 Faculty of Cultural Sciences, Universitas Gadjah Mada. It aims to investigate the variations of English pronunciation and errors related to 4 English diphthongs [eÉª], [aÉª], [ÉªÓ] and [eÓ] and to find out the factors that contribute to the erroneous pronunciation. This research involved 25 English Department students class of 2012, Faculty of Cultural Sciences, Universitas Gadjah Mada who were asked to read 40 sentences. Every sentence contains selected word that has a diphthong. This research also involves an expert from the English Department, Faculty of Cultural Sciences, Universitas Gadjah Mada to identify whether the pronunciation is acceptable or erroneous. The result of this research shows that the level of error in pronouncing the diphthong [eÉª] is 28%, [aÉª] is 6%, [ÉªÓ] is 24% and [eÓ] is 26%. In general, Indonesian learners did not have any difficulties in terms of pronunciation relating to 4 diphthongs [eÉª], [aÉª[ÉªÓ] and [eÓ].